HPTLC Method for Simultaneous Determination of Lopinavir and Ritonavir in Capsule Dosage Form - A. V. Sulebhavikar; U. D. Pawar; K. V. Mangoankar; N. D. Prabhu-Navelkar (E-Journal of Chemistry)
A rapid and simple high performance thin layer chromatography (HPTLC) method with densitometry at λ=263 nm was developed and validated for simultaneous determination of lopinavir and ritonavir from pharmaceutical preparation. Separation was performed on aluminum-backed silica gel 60F254 HPTLC plates as stationary phase and using a mobile phase comprising of toluene, ethyl acetate, methanol and glacial acetic acid, in the volume ratio of 7.0:2.0:0.5:0.5 (v/v) respectively. After development, plates were observed under UV light. The detector response was linear in the range of 6.67 to 20.00 µg/spot and 1.67 to 5.00 µg/spot for lopinavir and ritonavir respectively. The validated lowest limit of detection was 21.00 ng/spot and 5.10 ng/spot whereas lowest limit of quantification was 7.00 ng/spot and 21.00 ng/spot for lopinavir and ritonavir respectively. The percentage assay of lopinavir and ritonavir was found between 98.23 to 102.28% and 98.03 to 103.50% respectively. The described method has the advantage of being rapid and easy. Hence it can be applied for routine quality control analysis of lopinavir and ritonavir from pharmaceutical preparation and stability studies.